IMPLEMENTASI DISIPLIN KERJA DALAM PENINGKATAN KUALITAS SDM PADA OLAHRAGA KEBUGARAN INDONESIA (ORKI), TANGERANG - Irfan Rizka Akbar; Mitri Nelsi; Lily Setyawati Kristianti (Abdi Jurnal Publikasi, 2025)
The purpose of the Community Service activity is to implement one of the tri dharma of higher education. In addition, it is hoped that with community service, the existence of higher education can make a major contribution to the development and application of science to the community. The method used in this community service is in the form of counseling and coaching, namely in addition to better actions, processes and results or statements. In this case, it shows progress, increased growth, evolution of various possibilities, development or improvement of something. The results of community service obtained are to get development and Community Empowerment with the theme of Implementation of work discipline in improving the quality of human resources in Indonesian fitness sports, (ORKI), South Tangerang. The knowledge obtained can be developed again and disseminated in order to provide the best for the surrounding community.